2019
DOI: 10.12659/msm.915986
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Shear Stress Increases Osteocyte and Inhibits Osteoclasts via Downregulating Receptor-Activator of Nuclear Factor κB (RANK)/Osteoprotegerin Expression in Myeloma Microenvironment

Abstract: Background The aim of this study was to determine the effects of myeloma cells exposed to fluid shear stress on osteocytes and osteoclasts, and clarify the potential underlying mechanisms. Material/methods A flow and a non-flow model were established using a flow fluid chamber. The myeloma cell line U266 and murine osteocytic MLO-Y4 cells were cultured in vitro . The osteocytes and osteoclasts were examined under a microscope. Osteoclasts were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 22 publications
(23 reference statements)
2
12
0
Order By: Relevance
“…Recent in-vitro studies suggest that mechanical stimulation ameliorates the inhibitory effect of the MM microenvironment on osteocyte growth and a previous animal model confirmed that low intensity vibration protects bone quantity and quality and mitigates progression in a murine model of MM [45] , [46] . In wistar rats mechanical vibration increases bone density dependent of the vibration stimulus frequencies [47] .…”
Section: Introductionmentioning
confidence: 87%
“…Recent in-vitro studies suggest that mechanical stimulation ameliorates the inhibitory effect of the MM microenvironment on osteocyte growth and a previous animal model confirmed that low intensity vibration protects bone quantity and quality and mitigates progression in a murine model of MM [45] , [46] . In wistar rats mechanical vibration increases bone density dependent of the vibration stimulus frequencies [47] .…”
Section: Introductionmentioning
confidence: 87%
“…As a result, the bone in Gruen zone 7 bears less load and thereafter bone mass decreased significantly according to Wolff's law of mechanics 20 . Mechanical stress inhibited osteoclast proliferation through decreasing RANKL/OPG gene expression 21 . Raloxifene can bind to estrogen receptors and inhibit the activity of osteoclasts and, thus, make the bone density increase 10,12 .…”
Section: Discussionmentioning
confidence: 94%
“…However, the adverse effects were accompanied by its benefits, such as breast cancer and abnormal uterine bleeding. Fortunately, raloxifene, as a kind of SERM, has the potential to retain most of the beneficial effects of estrogen while avoiding most of the adverse effects 21 . Our results showed that using raloxifene for 2 years after THA did not increase adverse events, including cardiac events, stroke, venous thromboembolism, and gynecological cancer, and even decreased the odds of breast cancer, which is consistent with the descriptions in previous studies 18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the effects of different mechanical forces on osteoblasts and osteoclasts were investigated. Fluid shear stress reduced RANKL expression and increased OPG expression in cells, which significantly reduced the RANKL/OPG ratio, upregulating the expression of osteoblast marker genes [ 90 ] (Fig. 1 ).…”
Section: Mechanisms For Perceiving the Mechanical Environmentmentioning
confidence: 99%